The Optical Properties of Crystalline Zn3Nb2O8 Nanomaterials Obtained by Hydrothermal Method - Mihaela Birdeanu; Mirela Vaida; Eugenia Fagadar-Cosma (Journal of Chemistry)
The present study is focused on the obtaining of the Zn3Nb2O8 nanomaterial using the hydrothermal method and its characterization through different techniques. X-ray diffraction at room temperature revealed that a novel crystalline form of the nanomaterial forms at 1100°C belonging to monoclinic space group C2/c. Field-emission scanning electron microscopy evidenced the columnar morphology of the particle’s agglomeration and the high resolution electron transmission microscopy confirms the measured interplanar distances calculated from the X-ray diffraction experiments. Using the UV-VIS spectrum and Kubelka-Munk equations, the absorbance and the band gap for the Zn3Nb2O8 nanomaterial were calculated. PL spectrum reveals a single peak at 465 nm corresponding to the blue color fluorescence. The novel crystalline nanomaterial might find applications in fluorescence covering of technical devices, due to its capacity to preserve blue fluorescence both in acrylic based paint and after embedding in isopropyl alcohol.